2013
DOI: 10.1038/ng.2640
|View full text |Cite
|
Sign up to set email alerts
|

A functional variant in the CFI gene confers a high risk of age-related macular degeneration

Abstract: Up to half of the heritability of age-related macular degeneration (AMD) is explained by common variants. Here, we report the identification of a rare, highly penetrant missense mutation in CFI encoding a p.Gly119Arg substitution that confers high risk of AMD (P = 3.79 × 10⁻⁶; odds ratio (OR) = 22.20, 95% confidence interval (CI) = 2.98-164.49). Plasma and sera from cases carrying the p.Gly119Arg substitution mediated the degradation of C3b, both in the fluid phase and on the cell surface, to a lesser extent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
105
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 167 publications
(117 citation statements)
references
References 41 publications
7
105
1
Order By: Relevance
“…Given the dramatic reduction in transfusion requirements and the regular C3d depositions in almost all our patients, our data suggest that other factors are also involved in determining whether patients become transfusion independent. One possible explanation is individual genetic polymorphism in different complement regulators, such as factor H, 31,32 factor I, 33 complement receptor 1, 34 and even glycophorin itself, 35 that may be involved in the control of residual hemolysis. The association between allelic variants complement receptor 1 and transfusion dependence in patients receiving eculizumab has in fact been the subject of a recent publication.…”
Section: Discussionmentioning
confidence: 99%
“…Given the dramatic reduction in transfusion requirements and the regular C3d depositions in almost all our patients, our data suggest that other factors are also involved in determining whether patients become transfusion independent. One possible explanation is individual genetic polymorphism in different complement regulators, such as factor H, 31,32 factor I, 33 complement receptor 1, 34 and even glycophorin itself, 35 that may be involved in the control of residual hemolysis. The association between allelic variants complement receptor 1 and transfusion dependence in patients receiving eculizumab has in fact been the subject of a recent publication.…”
Section: Discussionmentioning
confidence: 99%
“…28 Therefore, these rare variant studies have provided important implications for causal SNPs or mutations related to AMD in the Chinese population. However, no mutated alleles for c.355G4A (p.(Gly119Arg)) 29 were detected in 192 of our AMD cases (data were not shown). The sample sizes of such studies must be scaled up because these low-frequency variants are not easily detected.…”
mentioning
confidence: 99%
“…Notably, the roles that rare CFI mutations have in the development of AMD were demonstrated in recent studies. 28,29 For example, van de Ven et al 29 identified a rare, highly penetrant missense mutation c.355G4A (p.(Gly119Arg); RefSeq NM_000204.3) that confers a high risk of AMD (OR, 22.20; P ¼ 3.79 Â 10 À6 ) via the regulation of C3b degradation. Although this likely causal mutation was also identified by Seddon et al, 28 the individual mutation showed no associations with AMD (P ¼ 0.24); 28 instead, the burden of rare functional CFI variant enrichment in this gene was significantly increased in AMD cases (OR, 3.6; P ¼ 2.0 Â 10 À8 ), indicating the combined effects of multiple rare mutations on the modulation of AMD risk.…”
mentioning
confidence: 99%
“…Recent studies suggest that at least a fraction of the "missing heritability" of AMD may be explained by rare variants with large effect sizes (Fig. 1) (Raychaudhuri et al 2011;Seddon et al 2013;van de Ven et al 2013;Zhan et al 2013). This shapes a new genetic architecture for AMD, encompassing both common genetic variants with relatively small effect sizes and rare genetic variants with large effect sizes.…”
Section: Discussionmentioning
confidence: 99%